2003
DOI: 10.1253/circj.67.643
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of Popliteal Artery Stents

Abstract: tent implantation in the peripheral arteries is a safe and effective treatment not only for obstructive diseases, but also non-obstructive conditions such as aneurysm formation. 1,2 More than 50% of all obstructive lesions are located in the femoropopliteal segment where they tend to be longer and have multiple coexisting atherosclerotic lesions at different levels. Surgical revascularization is the treatment of choice for these diffuse femoropopliteal stenoses and although percutaneous transluminal angioplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 15 publications
(17 reference statements)
1
57
0
Order By: Relevance
“…[19][20][21] The lack of broad acceptance for PA stent placement is mainly attributable to the fear of stent fractures, with possible subsequent restenosis in this vascular bed with high biomechanical stress next to the knee joint. 7,9,16,22,23 Published data support assumptions that stent design and technical aspects during stent deployment (eg, stent elongation, stent overlap) play major roles in the appearance of stent fractures. 6,8,9 However, the incidence of fractures in second-generation stents was low and ranged between 0% and 8.1% during a 1-year follow-up.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…[19][20][21] The lack of broad acceptance for PA stent placement is mainly attributable to the fear of stent fractures, with possible subsequent restenosis in this vascular bed with high biomechanical stress next to the knee joint. 7,9,16,22,23 Published data support assumptions that stent design and technical aspects during stent deployment (eg, stent elongation, stent overlap) play major roles in the appearance of stent fractures. 6,8,9 However, the incidence of fractures in second-generation stents was low and ranged between 0% and 8.1% during a 1-year follow-up.…”
Section: Discussionmentioning
confidence: 90%
“…Because of excessive mechanical forces applied to the PA during motion, the PA is considered a no-stent zone, and stent placement is currently reserved for suboptimal results after PTA, such as significant recoil, flow-limiting dissection, or significant residual stenosis. [7][8][9] The goal of this prospective, multicenter, randomized trial was to investigate the efficacy and safety of NS placement compared with PTA for the treatment of obstructive lesions in the PA.…”
Section: Circulationmentioning
confidence: 99%
“…The use of more flexible selfexpanding nitinol (shape memory alloy) stents has improved performances somewhat, but binary restenosis is still reported to be 24% at 6 months (compared with 44% for PTA alone) (Schillinger et al, 2006). Stent fracture has also been reported in case studies (Babalik et al, 2003, Solis et al, 2006, while a broader study showed a stent fracture rate of 24.5% in peripheral arteries at a mean follow up of 10 months (Scheinert et al, 2005). While almost half of the fractures were classified as minor (single strut fracture), a quarter were major (complete separation of stent segments) and a strong correlation was shown between stent fracture and restenosis.…”
Section: Introductionmentioning
confidence: 99%
“…BRS may also be suitable for vascular anatomy where scaffolds are prone to crushing and fractures, as seen in the femoral or tibial arteries. 43 Furthermore, BRS can obviate some of the other problems associated with use of permanent metallic stents such as the covering of side branches. BRS also appears to be compatible with noninvasive imaging such as CT angiography or MRI.…”
Section: Fully Bioresorbable Scaffold: the Potentialmentioning
confidence: 99%